2000
DOI: 10.1148/radiology.215.1.r00ap10286
|View full text |Cite
|
Sign up to set email alerts
|

Mammography with Synchrotron Radiation: Phase-Detection Techniques

Abstract: The authors evaluated the effect on mammographic examinations of the use of synchrotron radiation to detect phase-perturbation effects, which are higher than absorption effects for soft tissue in the energy range of 15-25 keV. Detection of phase-perturbation effects was possible because of the high degree of coherence of synchrotron radiation sources. Synchrotron radiation images were obtained of a mammographic phantom and in vitro breast tissue specimens and compared with conventional mammographic studies. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
155
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(156 citation statements)
references
References 18 publications
0
155
0
1
Order By: Relevance
“…The choice of mammography as clinical application was due to the relevance of this examination in the early diagnosis of breast cancer and to the limitations of conventional technique in terms of sensitivity and specificity, particularly with dense breasts [5]. Furthermore, the implementation of PhC mammography was somehow natural, taking into account the energy and geometrical characteristics of the X-ray beam available at SYRMEP.…”
Section: Clinical Mammographymentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of mammography as clinical application was due to the relevance of this examination in the early diagnosis of breast cancer and to the limitations of conventional technique in terms of sensitivity and specificity, particularly with dense breasts [5]. Furthermore, the implementation of PhC mammography was somehow natural, taking into account the energy and geometrical characteristics of the X-ray beam available at SYRMEP.…”
Section: Clinical Mammographymentioning
confidence: 99%
“…For this reason, the major effort of our research team has been oriented to study the effectiveness of PhC imaging using test objects and human breast tissue specimens [1,2,5]. The results of this pre-clinical phase were considered very successful [5].…”
Section: Clinical Mammographymentioning
confidence: 99%
See 1 more Smart Citation
“…1 With minor modifications to the conventional mammography geometry and x-ray tube anode spot size, PCM exploits the fact that changes in tissue density, which give rise to refractive index variations, can provide significant soft-tissue contrast from small structures even when conventional absorption contrast is low. [2][3][4] Indeed, preliminary studies using the Konica-Minolta REGIUS PureView TM system have demonstrated improved lesion detection from PCM when compared to conventional mammography. 5 However there remains a significant need for further system assessment and optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The in-line phase-contrast x-ray imaging is a technique using the free space diffraction of phase-shifted x-rays to form the interference fringes at tissues' boundaries and interfaces in images. [1][2][3][4][5][6][7][8] In fact, for over 100 years, the tissue attenuation differences have been the sole contrast mechanism for medical x-ray imaging. However, when x-rays traverse the body parts, as a wave x-rays undergo phase shifts as well.…”
Section: Introductionmentioning
confidence: 99%